ระดับโปรตีนที่เหมาะสมในอาหารสำเร็จสำหรับเลี้ยงหอยเป๋าฮื้อ Haliotis asinina linnaeus, 1758 ในระบบทดลองทางโภชนาการ - มนตรี อินทร์นวล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study the suitable protein level in the artificial diet for abalone Haliotis asinina Linnaeus in a nutritional requirement experimental system. The first experiment was designed to study the effect of 5 different levels of light intensity which were 400, 200, 100, 50 and 0 lux on shelter leaving behavior of abalone in the presence and absence of formulated diet. At 400 lux, no abalone was seen outside the shelter in the presence or absence of compound diet. More abalone left the shelter in the presence of diet than in the absence of diet at 200 and 100 lux. At 50 lux, abalone left the shelter no matter what the diet was presented or absented. Most of the abalone left the shelter when it was totally dark (0 lux). The second experiment was conducted to select the best attractant in the diet for abalone. Soybean meal, rice bran, spirulina and fish meal were chosen as attractants and compared to control diet (shrimp feed). The result revealed that fish meal was the best attractant for abalone diet. The third experiment was conducted to select the suitable shape and transparency of the experimental unit. Four different patterns of experimental unit were transparent rectangular shape, transparent cylindrical shape, opaque rectangular shape and opaque cylindrical shape. The result showed that the opaque rectangular shape was the most suitable pattern for the experimental unit. The last experiment was conducted to obtain the optimal protein level of the compound diet for abalone. Five different protein levels (35, 30, 25, 20 and 15%) and 2 lipid levels (0 and 5%) were assigned to formulate 10 test diets with a control diet (shrimp feed). The result revealed that the diet contained 30% protein and 0% lipid with gross energy of 396 kcal/100g and E/P ratio of 13:1 was the suitable diet for abalone Haliotis asinina under the experimental condition.